2006
DOI: 10.1681/asn.2005080894
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Ouabain Protect from Serum Deprivation–Triggered Apoptosis and Stimulate Kidney Cell Proliferation via Activation of NF-κB

Abstract: It now generally is agreed that Na,K-ATPase, in addition to its role in the maintenance of Na ؉ and K ؉ gradients across the cell membrane, plays a role in communicating information from the extracellular environment to intracellular signaling pathways. It was reported recently that interaction between ouabain-bound Na,K-ATPase and the 1,4,5-trisphosphate receptor (IP 3 R) triggers slow calcium oscillations and activation of NF-B. Here it is demonstrated that this signaling pathway can serve to prevent cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 47 publications
(48 reference statements)
5
88
1
1
Order By: Relevance
“…The similar origin of the cells suggests that the changes in ouabain response that were observed are a consequence of the cellular phenotype of normal renal epithelial cells versus mural cystic cells and not due to differences in the progenitor cell type. The proliferative effects of ouabain have been described in various cell types, including normal proximal tubule cells of the rat kidney (14,38). Although we could not detect statistically significant differences in the NHK cells, we observed a trend for an increase in ouabain-dependent proliferation in these cells.…”
Section: Discussioncontrasting
confidence: 70%
“…The similar origin of the cells suggests that the changes in ouabain response that were observed are a consequence of the cellular phenotype of normal renal epithelial cells versus mural cystic cells and not due to differences in the progenitor cell type. The proliferative effects of ouabain have been described in various cell types, including normal proximal tubule cells of the rat kidney (14,38). Although we could not detect statistically significant differences in the NHK cells, we observed a trend for an increase in ouabain-dependent proliferation in these cells.…”
Section: Discussioncontrasting
confidence: 70%
“…105 It has been shown that ouabain signals calcium oscillations through the inositol 1,4,5-triphosphate receptor that interacts with Na + /K + -ATPase and thereby induces NF-kB activation at concentrations that do not inhibit Na + /K + -ATPase activity. [107][108][109] In cardiac myocytes, ouabain has been reported to promote the rapid generation of reactive oxygen species, thereby inducing NF-kB activation. 110 As an early signaling pathway, Na + /K + -ATPase, on binding to cardiac glycosides, activates the cytoplasmic tyrosine kinase SRC, thereby activating the epidermal growth factor receptor and leading to the recruitment of adaptor proteins and the activation of the MAP kinase cascade that ultimately stimulates the mitochondrial production of reactive oxygen species.…”
Section: Cardenolide Glycosidesmentioning
confidence: 99%
“…59 We have found in studies performed on primary cultures of rat proximal tubular cells and on COS cells (a cell line derived from embryonic monkey kidney) that treatment with ouabain in concentrations that spare the pump function will result in translocation of NF-kB from the cytoplasm to the nucleus and reduced expression of I-kB, the cytosolic partner of NF-kB. 53,60 NF-kB consists of five subunits and is a pleiotropic transcription factor. 61 Dependent on the mode of activation, it may trigger transcription of the antiapoptotic factor Bcl-xL or the apoptotic factor apoptotic factor Bax.…”
Section: Slow Calcium Oscillations Activate Nf-kb and Protect From Apmentioning
confidence: 99%
“…61 Dependent on the mode of activation, it may trigger transcription of the antiapoptotic factor Bcl-xL or the apoptotic factor apoptotic factor Bax. 62 Ouabain-triggered calcium oscillations have, in studies on rat renal cells, been found to have an antiapoptotic effect 53,60 and to increase the expression of Bcl-xL.…”
Section: Slow Calcium Oscillations Activate Nf-kb and Protect From Apmentioning
confidence: 99%
See 1 more Smart Citation